Troglitazone (CS-045) normalizes hypertriglyceridemia and restores the altered patterns of glucose-stimulated insulin secretion in dyslipidemic rats - Chicco, Adriana Graciela (2000)
Rats fed a sucrose-rich diet ([SRD] 63% wt/wt) up to 270 days develop stable hypertriglyceridemia, impaired glucose tolerance, and insulin insensitivity. The aim of the present study is to Investigate whether the hypoglycemic agent troglitazone introduced as a pharmacologic intervention could improve and/or reverse the whole-body insulin insensitivity and related abnormalities present after feeding normal rats with a SRD long-term. For this purpose, male Wistar rats were fed a SRD for 210 days. While half of the animals continued with this diet for up to 270 days, troglitazone (0.2 g/dL wt/wt) was added to the SRD of the other half for up to 270 days. Troglitazone markedly reduced in vivo the hepatic triglyceride secretion rate (TGSR) and enhanced its removal from the circulation, leading to a normalization of plasma triglyceride levels. It also normalized the whole-body peripheral insulin resistance, the glucose homeostasis, and the elevated free fatty acids (FFAs) without detectable changes in plasma insulin levels. The clear alteration of the biphasic pattern of glucose-stimulated insulin secretion in the in vitro perfused β-cell islets of rats fed the SRD long-term (270 days) was also completely normalized when the SRD was supplemented with troglitazone for 2 months. The normalization of the altered patterns of glucose-stimulated insulin secretion, as well as the enhancement of peripheral insulin sensitivity without detectable changes in plasma insulin, might be largely a result of the significant action of troglitazone in the decrease of circulating lipids and enhancement of whole-body glucose metabolism. Copyright (C) 2000 by W.B. Saunders Company.